Value of serum C-reactive protein measurement in the management of bone marrow transplant recipients. Part I: Early transplant period. - Walker, S A (1984)
Serum C-reactive protein concentrations were measured serially during the early transplant period in 68 bone marrow recipients transplanted for leukaemia (34), chronic granulocytic leukaemia (2), severe aplastic anaemia (6), and various inborn errors of metabolism (26). There were 116 clearly documented episodes of infection or acute graft versus host disease or both. Serum C-reactive protein concentrations in patients with viral (11) or fungal infection (6) were normal or only slightly raised. In 32 patients with isolated acute graft versus host disease, only three (10%) showed serum C-reactive protein concentrations above 40 mg/l. Values greater than 40 mg/l were strongly suggestive of bacterial infections and values above 100 mg/l were seen only in patients (43) with bacterial infections with or without acute graft versus host disease. These findings suggest that serum C-reactive protein concentrations are valuable both for diagnosis and monitoring of such infections.